2017
DOI: 10.1007/82_2017_76
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Obstacles in the Genetic Dissection of Chlamydial Virulence

Abstract: Obligate intracellular pathogens in the family Chlamydiaceae infect taxonomically diverse eukaryotes ranging from amoebae to mammals. However, many fundamental aspects of chlamydial cell biology and pathogenesis remain poorly understood. Genetic dissection of chlamydial biology has historically been hampered by a lack of genetic tools. Exploitation of the ability of chlamydia to recombine genomic material by lateral gene transfer (LGT) ushered in a new era in chlamydia research. With methods to map mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 140 publications
0
9
0
Order By: Relevance
“…We screened a subset of heavily EMS-mutagenized Cm isolates using the murine GI and genital tract models of infection and identified a mutant, GIAM-1, that exhibited those characteristics. Unfortunately, the large number of nonsense mutations in GIAM-1 and the mutant's lack of a strong counterselectable in vitro phenotype have prevented us from identifying the attenuating mutations using markerless lateral gene transfer and/or complementation (49,50). Nonetheless, although we have screened only a small number of heavily mutagenized Cm isolates in the GI and genital tract infection models, those screens have identified the genital tract infection-attenuated GIAM-1 mutant and other mutants that are specifically attenuated for GI infection (28).…”
Section: Discussionmentioning
confidence: 99%
“…We screened a subset of heavily EMS-mutagenized Cm isolates using the murine GI and genital tract models of infection and identified a mutant, GIAM-1, that exhibited those characteristics. Unfortunately, the large number of nonsense mutations in GIAM-1 and the mutant's lack of a strong counterselectable in vitro phenotype have prevented us from identifying the attenuating mutations using markerless lateral gene transfer and/or complementation (49,50). Nonetheless, although we have screened only a small number of heavily mutagenized Cm isolates in the GI and genital tract infection models, those screens have identified the genital tract infection-attenuated GIAM-1 mutant and other mutants that are specifically attenuated for GI infection (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the transcriptional responses triggered in Chlamydia are not the same across different stress models, suggesting that specific Chlamydia genes participate in regulating the response to different stressful stimuli (Mathews et al, 2001; Belland et al, 2003; Gerard et al, 2004; Goellner et al, 2006; Ouellette et al, 2006; Maurer et al, 2007; Brinkworth et al, 2018). Due to Chlamydia being refractory to genetic manipulation until recently (reviewed in McClure et al, 2017; Brothwell et al, 2018; Rahnama and Fields, 2018), the genes involved in such response remain largely unknown. Notably, Muramatsu et al (2016) carried out a genetic screen aimed at identifying C. trachomatis mutants defective for recovery from IFNγ-induced persistence.…”
Section: Introductionmentioning
confidence: 99%
“…The diverse members of the phylum Chlamydiae constantly remain in the global spotlight, attracting attention not just as successful and enigmatic human and animal pathogens [1], but also by cutting-edge biological and "omics" research involving Chlamydiae [2,3]. From a global public perspective, Chlamydiae in Australia are perhaps best known as the notorious pathogens of the iconic marsupial, koala (Phascolarctos cinereus).…”
Section: Introductionmentioning
confidence: 99%